PENGARUH INTENSITAS KOMPETISI PASAR TERHADAP HUBUNGAN ANTARA PENGGUNAAN INFORMASI SISTEM AKUNTANSI MANAGEMEN DAN KINERJA UNIT BISNIS DAN KEPUASAN KERJA - YULIUS KURNIA SUSANTO; GUDONO GUDONO (Jurnal Bisnis dan Akuntansi, 2007)
This research examines the moderating effect of the intensity of market competition on the relationship between the usefulness of management accounting systems (MAS) information and business unit performance and job satisfaction. Fifty six business unit managers from manufacturing industry in Java and Sumatera had participated in this research. The collecting data used a questionnaire survey via electronicmail and post. Data were analyzed using a two-way analysis of variance. The results showed that the effects of the usefulness of MAS information on business unit performance and job satisfaction were dependent on the intensity of market competition. Under high levels of the intensity of market competition, the usefulness of sophisticated MAS information had a positive effect on business unit performance and job satisfaction, but under low levels it had a negative effect.